1997
DOI: 10.1021/jp962006+
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Mechanism of Surface Methoxy and Dimethyl Ether Formation from Methanol Catalyzed by Zeolitic Protons

Abstract: Density functional theory is used to study the zeolite acid catalyzed methanol dehydration to dimethyl ether. Three different reaction pathways are proposed. In the first, methanol adsorption and surface methoxy species formation are the initial elementary steps for this reaction. Subsequent dimethyl ether formation by reaction of a new methanol molecule with the surface methoxy species takes place. The second path involves the simultaneous adsorption and activation of two methanol molecules with formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
117
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(129 citation statements)
references
References 46 publications
12
117
0
Order By: Relevance
“…An obvious complication to this relatively simple, dualistic situation is that methanol always will be dehydrated to DME, quite often to the equilibrium ratio [20]. The mechanism of DME formation is well studied, and this reaction is also suggested to proceed via a direct or stepwise mechanism [21][22][23][24][25][26]. However, the mechanism of DME formation will not be discussed further, as its formation is quick compared to methylation [27] and several studies, both experimental and theoretical have shown that DME may undergo quite analogous reactions to those described above for methanol [12,27,28].…”
Section: General Considerations Concerning the Methylation Reaction Mmentioning
confidence: 99%
“…An obvious complication to this relatively simple, dualistic situation is that methanol always will be dehydrated to DME, quite often to the equilibrium ratio [20]. The mechanism of DME formation is well studied, and this reaction is also suggested to proceed via a direct or stepwise mechanism [21][22][23][24][25][26]. However, the mechanism of DME formation will not be discussed further, as its formation is quick compared to methylation [27] and several studies, both experimental and theoretical have shown that DME may undergo quite analogous reactions to those described above for methanol [12,27,28].…”
Section: General Considerations Concerning the Methylation Reaction Mmentioning
confidence: 99%
“…methanol that affect the route of n-hexane activation. Indeed, many mechanism studies of methanol conversion over zeolite have suggested that the possible intermediate species, such as methoxy groups or carbenium ion, display ionic character to some extent [7][8][20][21][22][23][24][25][26][27][28][29][30]. It seems that the intermediate species can more easily attack n-hexane molecules than Brønsted site of the zeolite surface.…”
Section: Proposed Reaction Pathway Of N-hexane Activationmentioning
confidence: 99%
“…Density functional theory (DFT) calculations of the adsorption of one methanol molecule onto an active site give activation energies in the range of 104-139 kJ mol −1 [5,8,9]. Blaszkowski and van Santen [10][11][12] showed that the simultaneous adsorption and activation of two methanol molecules towards the formation of DME and H 2 O excluding surface methoxy group formation is the preferred pathway. However, surface methoxy groups have been readily observed with stopped flow NMR studies over ZSM-5 catalysts [13].…”
Section: Introductionmentioning
confidence: 99%